Comparision of dexmedetomidine and clonidine with hyperbaric bupivacain in spinal anaesthesia - Agrawal, Anshul; Jain, Sunita; Goyal, Ashish (International Surgery Journal, 2021)
Background: Alpha-2 adrenergic agonists used as adjuvant to spinal anaesthesia produce substantial sensory and motor blockade of bupivacaine. This study was planned to compare the sensory and motor blockade characteristics of intrathecal combinations of adjuvants dexmedetomidine and clonidine with hyperbaric bupivacaine in the cases who underwent lower limb surgery under spinal anaesthesia. Methods: This was prospective, randomized, double blind study. 90 patients of age group between 18-60 years, ASA grade I and II were allotted into 3 equal groups. Group B received 15 mg bupivacaine plain, group BD and BC received dexmedetomidine (5mcg) and clonidine (50mcg) as adjuvants to bupivacaine respectively. Results: The duration of 2 dermatome regression time, sensory blockade and motor blockade were longest in dexmedetomidine group (129.37±4.87; 386±58.43; 353±48.87) in compared to clonidine (109.77±5.95; 296.53±57.19; 269.7±51.2) and bupivacaine group (81.03±6.83; 211.1± 30.47;181.03±20.8). Both drugs do not affect the peak level of sensory blockade, sensory block onset and motor block onset time. Dexmedetomidine and clonidine do not cause sedation in intraoperative and postoperative period. Conclusions: We conclude that addition of dexmedetomidine and clonidine in spinal anesthesia with hyperbaric bupivacaine increase the duration of ‘2 dermatome regression’ time, sensory and motor blockade and both are more with dexmedetomidine than with clonidine.